Megakaryocytic hyperplasia in myeloproliferative neoplasms is driven by disordered proliferative, apoptotic and epigenetic mechanisms. Issue 2 (19th August 2015) - Malherbe, Jacques A J; Fuller, Kathryn A; Arshad, Ayesha; Nangalia, Jyoti; Romeo, Giuliana; Hall, Sara L; Meehan, Katie S; Guo, Belinda; Howman, Rebecca; Erber, Wendy N
Abstract : Aims: Myeloproliferative neoplasms (MPN) are a heterogeneous group of clonal proliferative bone marrow diseases characterised by extensive megakaryocytic hyperplasia and morphological atypia. Despite knowledge of genomic defects, the pathobiological processes driving these megakaryocytic abnormalities in MPN remain poorly explained. We have explored the proliferative, apoptotic and epigenetic profiles of megakaryocytes in human MPN. Methods: Immunohistochemical staining was performed on bone marrow trephine biopsies of 81 MPN (with and without JAK2 V617F and CALR mutations) and 15 normal controls to assess the megakaryocytic expression of biomarkers associated with proliferation (Ki67), apoptosis (Bcl-XL, BNIP-3) and epigenetic regulation (EZH2, SUZ12). Results: Myeloproliferative megakaryocytes showed significantly greater expression of proliferative Ki67 and anti-apoptotic Bcl-XL, reduced pro-apoptotic BNIP-3 and increased SUZ12 compared with controls. In essential thrombocythaemia, large-giant megakaryocytes with hyperlobated nuclei showed a trend towards a proliferative signature. In contrast, myelofibrotic megakaryocytes with condensed nuclear chromatin, and cases with CALR mutations, had significant reductions in pro-apoptotic BNIP-3. Conclusions: Uncontrolled megakaryocytic expansion in MPN results from a combination of increased proliferation, attenuated apoptosis and defective epigenetic regulation with CALR mutations favouring apoptotic failure. The higher platelet counts reported to be seen in MPN with CALR mutations may be due to greater dysregulation of megakaryocyte apoptosis.